Kierunek / "Solidarność" . pismo Komitetu Porozumienia Międzyzakładowego "Solidarność", no. 24, 1982 - "Solidarność", [ed. Mikołaj Niegosz] (s.n.], 1982)
Creation and circulation: Issues no. 1-5,7,9,12-13,16(1982) contain a list of new independent periodicals.